Implementation Of Educational Discipline In Synergy Between Parent and Teacher In Schooling In Babussalam Lombok East SMK - Ariani, Silvia (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
The purpose of this research is to further describe how the implementation of the character education discipline students. The type of research used is a qualitative approach that uses descriptive methods, data collection techniques that are observations, interviews and documentation. Primary data sources are obtained from observations and interviews with teachers, head of school and some parents of pupils, and primary data resources are derived from previous research journals that investigate disciplinary character education. The results of the research showed that there are four ways that schools are trying to support student character education, namely, performing character education programming at school, setting up school rules and class rules, monitoring student disciplinary behavior at home Through the recording of daily activities and the involvement of parents in supporting the character education programme of this discipline by the school.